Key Competencies as a Source of Long-Term Competitive Advantages of Companies in International Markets - Ippolitova, Inna; Serhiienko, Olena; Airapetov, Mykhailo; Oglu, Rovshan Guliyev Haji; Rassadnykova, Svitlana (Theoretical and Practical Research in Economic Fields; Vol 17 No 1 (2026): TPREF Volume XVII Issue 1(37) March 2026, 2026)
The aim of the study is to build a quantitative model of the impact of key competencies on the long-term competitiveness of companies in the international economy. The analysis covers data from 30 companies from Germany, Japan, the USA, Poland, Ukraine, and France for 2022–2024. The sample includes companies from the mechanical engineering, logistics, IT, pharmaceuticals, and retail sectors - sectors that play an important role in the international economy. The study uses a panel econometric model with fixed effects, which includes indicators of competencies, digital transformation, Human Resources Development (HRD), innovation, and international experience. The results confirmed a statistically significant positive impact of key competencies on competitive advantage: the highest LCA values were observed in the USA (up to 88.2), Germany (up to 86.1), and France (up to 83.9). A stable increase in competitiveness is recorded in companies with a high level of digitalization and competency development. The findings confirm the importance of competencies as a long-term strategic resource in the international economy. The article emphasizes the need for institutional stimulation of the development of key competencies in companies to increase their competitiveness in global markets.